Representation of Women in Demi Nama Baik Kampus Short Films from Sara Mills’ Perspective - Wibawani, Sri; Anwar, Miftahulkhairah (Journal of Pragmatics and Discourse Research, 2023)
This study aims to reveal the representation of women in the short film Demi Nama Baik Kampus from the perspective of Sara Mills' critical discourse analysis. This research includes descriptive qualitative research with a critical paradigm. The research data are characters' speeches that show the form and meaning of actors' positions, while the data source comes from the short film Demi Nama Baik Kampus. The data collection was done by a note-taking technique that refers to Sara Mills' critical discourse analysis theory. The results showed that (1) the subject position is occupied by Sinta; (2) the object position is occupied by Mr. Rector and Mr. Arie; and (3) the audience position is directed to take themselves from the perspective of Sinta as a victim of sexual harassment who was silenced for the sake of maintaining the good name of the campus. At the end of the story, women are represented as brave, persistent, tough, strong, and powerful. In general, the implications of this research emphasize a more positive paradigm, inspire more responsible and inclusive media use, and promote the development of narratives that support gender equality and women's empowerment.Keywords: representation, women, short films, Sara Mills